Combining single‐use stirred bioreactor with standard cross‐flow technology in biphasic protein production processes at pilot scale. Issue 3 (6th January 2014) - Blaschczok, Katharina; Löffelholz, Christian; Eibl, Regine; Eibl, Dieter
<x xml:space="preserve">Abstract</x> The increasing implementation of single‐use bioreactors arrived hand‐in‐hand with the development of new technologies contributing to increased productivity, process flexibility, and additional savings in time and costs. As a result, hollow fiber technology has recently gained renewed interest in upstream processing. Using a Chinese hamster ovary cell line in a biphasic protein production process with chemically defined minimal culture media, we combined Sartorius Stedim's BIOSTAT STR 50 L with GE Healthcare Life Sciences' reusable Hollow Fiber Cartridge CFP‐6‐D‐55A. After a 3‐day feeding growth phase, secretion of the model protein secreted alkaline phosphatase (SEAP) was introduced by replacing the growth medium with production medium using cross‐flow filtration. The process was then continued and harvested as a batch with temperature shift. High cell densities exceeding 1 × 107 cells mL−1 were achieved 5 days post inoculation and maximum secreted alkaline phosphatase activities of 24 U mL−1 11 days post inoculation. Our results showed that a further decrease in processing time is possible by reducing the number of diafiltration steps from three to two.